Metodologija za oceno pomembnosti sestojev za ohranjanje biotske raznolikosti v gozdni krajini - Papež, Jože (Gozdarski vestnik, 2008)
The article proposes theoretical starting-points for evaluation methodology ofstand importance for sustaining biodiversity in forest landscape. The methodis based on the use of data acquired in elaborating forest management plans; according to the authors' opinion it can facilitate decisions required for making forest management and growing plans and monitoring of biodiversity.
Keywords: ekologija gozda; biodiversity; biotska raznovrstnost; gozdnogospodarski načrti; lesna zaloga; lesana biomasa